SECURITY AUDIT FOR DETECTION AND MITIGATION OF AMP INJECTION FROM ONLINE GAMBLING SITES ON THE WORDPRESS PLATFORM WITH A CODE ANALYSIS AND WORDFENCE SCANNING APPROACH - Fathur Fawaz, Muhamad; Nugraha, Yopi (RISTEC : Research in Information Systems and Technology, 2025)
This study discusses issues with AMP injection that are not present on WordPress-based websites, which affect serious issues like navigating to a website in another language and exploiting user data. In this study, we examine the main causes of AMP infiltration, such as improperly modified WordPress core files, and offer suggestions for improvement and correction. The research methods that are used include analyzing the WordPress code sumber, keeping track of files using keamanan tools, and implementing mitigation solutions to ensure the integrity of the core files. The results of the study highlight the importance of careful attention to WordPress files and the use of strong security tools in order to prevent more extensive exploitation. This research provides useful information for WordPress site owners to monitor security and identify non-detectable security risks.